The Binomial - Medicine/Art [In Bulgarian] - E. Pavlov (University of Sofia, 2008)
The article considers the binomial - medicine/art. Medical treatment of body should be combined with the medical treatment of soul. 'A sound mind in a sound body' can be achieved when art supports medicine. Semiotic aspects of medicine are discussed. The introduction of such ideas to medical education is recommended.